Sistem Informasi Pengangkutan Pupuk Menggunakan Metode Waterfall (Studi Kasus PT. Pupuk Iskandar Muda, Aceh Utara) - M Fauzan Azrial azrial; Nurul Fadillah (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2020)
Information systems are a set of elements that are interconnected with each other and work together to achieve a goal so that they can integrate data, process and store and distribute information. Fertilizer transportation information system at PT. Pupuk Iskandar Muda makes the processing of fertilizer transportation and transaction data become computerized which is equipped with features to create reports and can display recapitulations and visualizations in the form of graphs of total transactions. Through this system, warehouse, fertilizer, transportation and fertilizer supply data processing can also be carried out. Total transportation in 2019 from 01-01-2019 to 31-12- 2019 Total 26 times, with a total transported of 42 tons, 5 units of transporters, and a total payment of Rp. 73,350,000Keywords: abstract keywords.